Superior Degradation Performance of Nanoporous Copper Catalysts on Methyl Orange - Jinyi Wang; Sen Yang (Metals, 2021)
The development of low-cost and high-efficiency catalysts for wastewater treatment is of great significance. Herein, nanoporous Cu/Cu2O catalysts were synthesized from MnCu, MnCuNi, and MnCuAl with similar ligament size through one-step dealloying. Meanwhile, the comparisons of three catalysts in performing methyl orange degradation were investigated. One of the catalysts possessed a degradation efficiency as high as 7.67 mg·g−1·min−1. With good linear fitting by the pseudo-first-order model, the reaction rate constant was evaluated. In order to better understand the degradation process, the adsorption behavior was considered, and it was divided into three stages based on the intra-particle diffusion model. Three different temperatures were applied to explore the activation energy of the degradation. As a photocatalytic agent, the nanoporous structure of Cu/Cu2O possessed a large surface area and it also had low activation energy, which were beneficial to the excellent degradation performance.